Innovative Connection of Steel Profiles, Experimental Verification and Application. (2017) - Flodr, Jakub; Kałduński, Paweł; Krejsa, Martin; Pařenica, Přemysl
Abstract: Paper wants to focus on the issue of joining steel structures and the use of new methods in civil engineering. Clinching method is a very interesting alternative to joining steel elements to increase efficiency and simplification. Currently it is not possible to check these types of connections according to the official methodology for civil engineering. Without verification of specific joint by physical experiment it is not possible to use these checked connections in building structures. Attention will be paid to the connection of thin walled elements. This work should be the basis for a methodology for design and check of these joints.